Design of rock support system under rockburst condition - Kaiser, Peter K.; Cai, Ming (Journal of Rock Mechanics and Geotechnical Engineering, 2012)
As mining and civil tunneling progresses to depth,excavation-induced seismicity and rockburst problems increase and cannot be prevented.As an important line of defense,ground control measures and burst-resistant rock support are used to prevent or minimize damage to excavations and thus to enhance workplace safety.Rock support in burst-prone ground differs from conventional rock support where controlling gravity-induced rockfalls and managing shallow zones of loose rock are the main target.Rock support in burst-prone ground needs to resist dynamic loads and large rock dilation due to violent rock failure.After reviewing the rockburst phenomenon,types of rockbursts,damage mechanisms,and rockburst support design principles and acceptability criteria,this paper describes that the support selection process in burst-prone ground is iterative,requiring design verification and modification based on field observations.An interactive design tool for conducting rockburst support design in underground tunnels is introduced to facilitate cost-effective design.